Cancer risk after bariatric surgery — is colorectal cancer a special case?. Issue 11 (November 2018) - Hull, Mark; Markar, Sheraz; Morris, Eva
Bariatric surgery-induced weight loss is associated with reduced overall cancer incidence; however, some data suggest that risk of colorectal cancer (CRC) actually increases. Here, we suggest a need to fully characterise CRC (and colorectal adenoma) risk after bariatric surgery given that preventive measures (early diagnosis and polypectomy) can mitigate risk.